Social play among black and gold howler monkey (Alouatta caraya) immatures during intergroup encounters - Gennuso, María Sol (2018)
We studied intergroup social play (IGSP) among immatures in wild black and gold howler monkeys (Alouatta caraya) in northeastern Argentina. IGSP events are one form of affiliative interaction that can occur during intergroup encounters. The main goal of this study was to analyze IGSP in A. caraya immatures and assess how intrinsic (e.g., age and sex) and extrinsic (e.g., seasonality) factors can influence the development of this type of social behavior. We followed 12 groups between 2008 and 2015 and recorded 182 encounters and 61 events of IGSP. Considering the composition of play partners, most IGSP events occurred among juveniles of both sexes (33%), followed by juveniles that were only-male (31%), and finally between mixed-sex juveniles and infants (20%) interactions. Additionally, most IGSP events occurred mainly in summer (56%), followed by spring (29%), with fewer events occurring in autumn (15%) and no IGSP events recorded in winter. Our results suggest that IGSP constitutes a beneficial activity in wild A. caraya that promotes behavioral flexibility, where immatures acquire social skills, such as tolerance, by interacting with unknown individuals. Moreover, the higher participation of young males in IGSP is consistent with the fact that adult black and gold howler males tend to be more actively involved in group encounters than females, supporting the hypothesis that social play provides benefits in the development of motor and social skills. Finally, seasonality in the frequencies of IGSP might be related to availability of foods with high and easily mobilized energy content in summer and spring.